PENGETAHUAN TENTANG MENSTRUASI MEMBENTUK SIKAP POSITIF PERSONAL HYGIENE REMAJA PUTRI - Rizky Fadilasani; Hariadji Sugito; Purnamasari, Desy (WOMB Midwifery Journal, 2023)
The reproductive health problems of women in their teens that rank highest in the world are poor personal hygiene, around 35-42%. Personal hygiene during menstruation is an effort to maintain cleanliness during menstruation for physical and psychological health, supported by good knowledge related to menstruation. The aim of the study was to analyze the relationship between menstrual knowledge and personal hygiene attitudes during menstruation for teenage girls at SMAN 1 Genteng Banyuwangi in 2022. This research was an observational analytic study with a cross-sectional design. A sample of 83 respondents used the slovin formula with a simple random sampling technique. The instruments used were knowledge questionnaires and attitude questionnaires on a Likert scale. Data analysis used Fisher's Exact Test with SPSS 24 for windows. Adolescent girls have good knowledge (87.9%) and positive personal hygiene attitudes during menstruation (86.7%). The results showed that there was a relationship between knowledge of menstruation and personal hygiene attitudes during menstruation in female adolescents at SMAN 1 Genteng Banyuwangi in 2022 (P 0.000 <0.05). It is hoped that the synergy between the school UKS and health workers will conduct counseling about personal hygiene during menstruation so that young women will receive relevant information.